PENGARUH PERAWATAN LUKA MENGGUNAKAN GEL LIDAH BUAYA TERHADAP KESEMBUHAN DEKUBITUS - Erika Erika; Rahma Fridayana Fitri; Ainyia Sumiati (Journal of Indah Science and Clinic, 2021)
Decubitus has recently become a problem in both developed and developing countries, especially Indonesia. Until now, pressure sores are still a classic problem in the health sector, especially in the nursing field. In Kebumen Hospital, 38.18% of patients had pressure sores. Damage to skin integrity caused by bed rest, if left unchecked for a long time will irritate the skin until the formation of wounds on the skin, therefore tissue undergoing necrosis due to lack of blood supply to certain tissues. Nowadays, this is a secondary affliction experienced by many hospitalized patients. This paper aims to determine the effect of wound care using aloe vera gel on the healing of decubitus performed on 10 people in Tanjung Rejo Village, Percut Sei Tuan, Deli Serdang. This study used an experimental method by looking at the cure rate given by aloe vera gel and before being given aloe vera gel, moreover, for the response given aloe vera gel and not. Based on the output of the Mann-Whitney test, it is known that the p-value is 0.008 < (? = 0.05), so it can be concluded that there is a difference between the control group and the treatment group. Because there is a significant difference, it can be assumed that there is an effect of giving aloe vera gel on the healing process of decubitus wounds.